Analysis of Digital Marketing Strategies in MSMEs in Banda Aceh to Increase Competitiveness in the Post-Pandemic Era - Wanda, Edi; Maulidar; Hijriatin, Maudi (Divisi Riset, Lembaga Mitra Solusi Teknologi Informasi (L-MSTI), 2024)
Digital transformation has become one of the main challenges for Micro, Small and Medium Enterprises (MSMEs) in Indonesia, especially in dealing with post-pandemic market dynamics. This study aims to analyze the digital marketing strategies implemented by MSMEs in Banda Aceh in order to increase competitiveness in the digital era. The research method used is a descriptive method with a quantitative approach. Primary data was collected through a survey of 50 MSME players who actively use digital platforms, such as social media, marketplaces, and business applications. Secondary data was obtained from related agency reports and literature studies. The results showed that the majority of MSMEs in Banda Aceh have utilized social media, such as Instagram and WhatsApp Business, as the main channel for digital marketing. The most commonly used strategies include visual promotional content, time-based discounts and direct interaction with customers. However, significant challenges remain, such as limited understanding of technology, limited marketing budgets, and low utilization of customer data for consumer behavior analysis. This study concludes that the adoption of digital marketing can significantly improve MSME competitiveness, especially in expanding market reach and increasing customer loyalty. Strategic recommendations include improving digital literacy through training, utilizing analytics tools to understand consumer behavior, and collaborating with local communities to strengthen business networks. The findings are expected to provide practical contributions for MSME players in Banda Aceh as well as a reference for policy makers in supporting digital transformation in the MSME sector.